OSVALDO ROMO’S NOTEBOOKS. DOUBTS AND CHALLENGES FOR THE DOCUMENTARY ARCHIVE OF THE PARK FOR PEACE VILLA GRIMALDI - Sagredo Mazuela, Omar; Rubio Urrejola, Nathalia (Revista de Historia Social y de las Mentalidades, 2020)
This article describes and analyzes the process of incorporating Osvaldo Romo Mena’s notebooks (deceased civil agent of the Directorate of National Intelligence) into the Archive of the site of memory Parque por la Paz Villa Grimaldi. Unlike the general perspective of human rights archives in Chile, regarding disclosure, accessibility and use, these documents present an additional challenge: their veracity. It is proposed to study this issue from a double dilemma: as a problem in the field of human rights archives and as a controversial situation associated with the “doubt” that the study about perpetrators represents for research in a site of memory.